UTILIZATION CRYSTAL VIOLET AS NUCLEI DYE IN HISTOPATHOLOGY OF BREAST CANCER - Mamay, Mamay; Apriyadi, Yadi; Nurisani, Astari; Hardianti, Dian (Jurnal Medika Cendikia, 2023)
Microscopic examination of cancer development can be identified through histopathological examination. Hematoxylin–eosin (HE) is the gold standard for staining method. This processing can be obstructed if hematoxylin reagent out of stock in the laboratory. Other reagents are needed that can replace the use of hematoxylin, one of which is crystal violet. This study aims to evaluate the use of crystal violet as a nuclei stain in breast cancer preparations. The research sample consisted of 15 breast cancer preparations taken at the sample bank in the anatomical pathology laboratory of RSUD Dr. Slamet Garut. The results showed that from 15 preparations, it was observed that 4 preparations (27%) stained worth and 11 preparations (73%) stained poorly. Based on the research results, crystal violet crystal violet has a low core coloring ability in breast cancer preparations. From the results of this study, it is recommended to modify the crystal violet reagent by paying attention to the acidity of pH and concentration of crystal violet.